Indonesian Language Teaching and Education Among The Millennial Generation - Cecep Wahyu Hoerudin (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
Researchers are researching how and what factors can help millennials learn Indonesian correctly and adequately. In the end, Indonesian is not only taught in classes but also understood and loved and becomes an identity for millennial teenagers. This research will be carried out using a qualitative approach as the method. The data of this research were obtained through various results of previous studies and studies that are still related and related to this research. The millennial learning model requires teachers to have personality, social, educational, and professional competencies related to the linguistic field. Students are complex individuals about physical, emotional, spiritual, moral, cultural, social, and intellectual development. The proper steps include the correct use of media in educating the millennial generation through electronic tools and the internet. There are many challenges in educating the millennial generation, such as maintaining millennial youth’s values and positive characteristics for education. Finally, educators also need to develop the attitude of these millennials in their critical attitude through the provision of materials and the use of appropriate media.